2016
DOI: 10.3748/wjg.v22.i13.3581
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D and colonic vitamin D receptor in inflammatory bowel disease

Abstract: Levels of serum vitamin D correlate positively with colonic VDR expression in visually normal mucosa whereas inflammation correlates negatively with colonic VDR expression in visually diseased mucosa in Puerto Rican patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
2
33
2
2
Order By: Relevance
“…In contrast to findings in humans with IBD, which have significantly decreased intestinal VDR expression, 39,52 we found no difference in VDR expression in the duodenum of dogs with gastrointestinal inflammation. Assessments of inflammation by several criteria and by multiple methods showed no significant decline in VDR (Fig 4).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to findings in humans with IBD, which have significantly decreased intestinal VDR expression, 39,52 we found no difference in VDR expression in the duodenum of dogs with gastrointestinal inflammation. Assessments of inflammation by several criteria and by multiple methods showed no significant decline in VDR (Fig 4).…”
Section: Discussioncontrasting
confidence: 99%
“…The second major finding of this study was that duodenal VDR expression, both RNA and protein, did not decrease with inflammation. This contrasts with the changes reported in both human and rodent colonic inflammation …”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Furthermore, Abreu-Delgado et al[65] reported that levels of serum vitamin D correlate positively with colonic VDR expression in visually normal mucosa; whereas inflammation correlates negatively with colonic VDR expression in visually diseased mucosa. The VDR needs further research.…”
Section: Ibd- and Autophagy-related Genetic Variantsmentioning
confidence: 99%